FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS LABA DENGAN KEPEMILIKAN MANAJERIAL SEBAGAI PEMODERASI - Sandra, Veronica; Lukman, Hendro (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
This study aims to analyze the effect of prudence and growth on earnings quality with managerial ownership as a moderator in manufacturing companies in the Consumer Non-Cyclicals sector listed on the Indonesia Stock Exchange (IDX) with an observation period of 2018-2021. The sample technique used is purposive sampling where the total sample after outliers is 30 companies with a total of 115 data. The analysis technique used in this study is moderating regression analysis using IBM SPSS Statistics Version 22 to process data and Microsoft Excel 2016 to collect data. The results shown in this study indicate that prudence and growth have no effect on earnings quality. Thus the role of managerial ownership as a moderator weakens the effect of prudence and growth on earnings quality. The implication of this research is that companies need to manage their CFO (Cash Flow Operations) well to improve earnings quality.